Angiogenesis-related gene NID2 profiling and immune infiltration in bladder cancer: prognostic implications and immunotherapy response - Cao, Jinxia; Zheng, Wang (Frontiers in Immunology, 2025)
BackgroundImmunotherapy has progressively gained prominence as a cornerstone therapeutic modality across diverse oncological contexts, with its clinical efficacy intricately linked to the dynamic interactions between the tumor microenvironment (TME) and neoplastic cells. Central to this paradigm is angiogenesis—a quintessential hallmark of cancer—which not only sustains tumor growth but also orchestrates immunomodulatory networks within the TME, thereby profoundly influencing therapeutic responsiveness. However, in the field of bladder cancer (BC), the relationship among angiogenesis and prognosis, immunotherapy response, and immune cell infiltration remains to be further explored.MethodsTo systematically uncover this relationship, we carried out an exhaustive assessment of 36 genes linked to angiogenesis (AAGs) and explored the relationship between angiogenesis and transcript, prognostic outcomes, as well as the infiltration of immune cells. By constructing an AAG_score, we quantified the angiogenic subtype characteristics of each patient. Subsequently, we evaluated the value of these characteristics in foreseeing BC prognosis and the response of treatment, and concurrently analyzed the performance of AAGs in diffuse large B-cell lymphoma for comparative study. Through RT-qPCR, CCK8 and other experiments, we verified the role of NID2 in bladder cancer.ResultsThis study explored different types of AAGs mutations in BC samples at the genetic level and elucidated the expression patterns of AAGs. Through in-depth analysis, we identified two distinct molecular subpopulations and found significant associations between AAG mutations and patients’ clinicopathological features, prognosis, and invasive TME. We found that patients with low AAG_score showed increased microsatellite instability, high mutation tendency, and immune motivation, and had a better prognosis. NID2 plays a role in promoting proliferation in bladder cancer and evaluate in diffuse large B-cell lymphoma. In addition, our study found a significant correlation between index of cancer stem cell and AAG_score in drug sensitivity.ConclusionIn summary, our study successfully identified prognosis-related AAG characteristics in BC patients. These characteristics not only contribute to a clearer understanding of TME properties but also provide an important basis for exploring more effective immunotherapy strategies.